Comparative studies of physical characteristics of raw and modified sawdust for their use as adsorbents for removal of acid dye - Singh J.; Mishra N.S.; Uma; Banerjee S.; Sharma Y.C. (My University, 2025)
The present paper aims to investigate the physical characteristics of sawdust relative to its use as an adsorbent for removal of an acid dye (Orange G) from aqueous solutions. The raw sawdust was sieved to have a uniform size and was activated by sulphuric acid by refluxing the content at 60 °C for 4 h. Surface morphology and surface functional groups of both raw and modified sawdust samples were investigated by Scanning Electron Microscope (SEM), Energy Dispersive X-ray Analysis (EDX), Fourier Transformation Infrared (FTIR), and elemental analysis. All these analyses displayed significant change in the structure of the sawdust. The data obtained from batch adsorption experiments for the removal of the selected dye confirmed that adsorption characteristics of the modified sawdust were better than those of raw sawdust.